Investigating steel tool life in the RFSSW process. (October 2020) - Larsen, Brigham; Hunt, John; Hovanski, Yuri
Abstract: Refill Friction Stir Spot Welding (RFSSW) has demonstrated capability in joining thin sheets of aluminum with dissimilar thickness, alloy, and composition. The process remains to be implemented on a wide scale in the automotive and aerospace industries, partially due to the relatively short number of welds producible by a toolset, prior to needing cleaning. In the following work, an investigation was conducted to better understand this limitation. First, the effective tool life of a steel toolset was quantified. Experiments showed that less than 60 consecutive welds could be made before the toolset seized and required cleaning. To better understand the conditions contributing so such a short tool life, thermocouples were used in subsequent experiments, to measure the temperatures achieved at various locations in the weld. Peak weld temperature increased with longer cycle times and decreased with shorter cycle times. During the experiments, it was noted that weld temperatures in excess of 500 °C were observed at weld center. At these high temperatures, the authors anticipate that intermetallic compounds (IMCs) are able to grow on tool surfaces. A rough, existing model of IMC growth in an Fe-Al system predicted IMC growth on the same order of magnitude of the tool clearances, supporting the anticipation that IMC growth is a factor in the observed, short tool life between cleanings. Following this analysis, future evaluation of less re-active tool materials is recommended.